SPATIAL OUTLIERS DETECTION ALGORITHM (SODA) APPLIED TO MULTIBEAM BATHYMETRIC DATA PROCESSING - Ferreira, Italo Oliveira; Santos, Afonso de Paula dos; Oliveira, Júlio César de; Medeiros, Nilcilene das Graças; Emiliano, Paulo César (Boletim de Ciências Geodésicas, 2018)
The amount of data produced in an echo sounder has grown exponentially with scanning systems such as multibeam echo sounders and interferometric sonars, providing a considerable improvement in the submerged relief representation, especially to detect hazard objects to the navigator. However, the available processing algorithms did not follow this evolution; manual processing is usually necessary or at least constant intervention by an analyst, making this task arduous with a high subjectivity degree. In addition, statistical inconsistencies are common in most of the algorithms and filters available. Thus, SODA (Spatial Outliers Detection Algorithm) was recently presented, which is a methodology directed at first for echo sounder data treatment. The authors evaluated the algorithm efficiency using simulated data. Therefore, this article aimed to evaluate the SODA efficiency for real data treatment, with a multibeam echo sounder. A number of interesting results was obtained, reaffirming the methodology strength, regarding the search for spikes in echo sounder data.